DAMPAK DAN PENGARUH PERTAMBANGAN BATUBARA TERHADAP MASYARAKAT DAN LINGKUNGAN DI KALIMANTAN TIMUR - Yosana Zalukhu, Frendly Albertus dan (Universitas 17 Agustus 1945 Samarinda, 2019)
A social problem tells of the difficulties, especially a number ofresidents in East Kalimantan to obtain welfare, a healthy environment,and agricultural land that can be used to make a living. Steam powerplant construction projects are one of the causes of coal mining. Where itwill bring the positive side, that the community needs electricity, but onthe other hand will affect the natural resources that are around thedisruption of community activities that are farming and gardening. EastKalimantan is the largest coal producer in Indonesia and has high naturalresource potential. Coal itself is a non-renewable natural resource and ifit is continuously extracted it will affect the environment and waterresources. In the regulation of the Minister of RI No. 26 of 2018, article20 paragraph 2b reads